Ferroptosis in periodontitis: mechanisms, impacts, and systemic connections - Peng Guan; Qijun Ruan; Jiatong Li; Mengying Xi; Weijuan Qi; Kang I. Ko; Jia Ni (Cell Death Discovery)
Abstract Periodontitis is a chronic inflammatory disease initiated by plaque microorganisms, with the regulatory mechanisms of its progression being a primary research focus. Ferroptosis, a unique form of cell death driven by iron-dependent lipid peroxidation, has been increasingly recognized for its crucial role in modulating chronic inflammation. This study focused on the molecular mechanisms by which plaque microorganisms and the inflammatory microenvironment trigger ferroptosis in periodontal cells, elucidating how ferroptosis in these cells promotes periodontitis progression. Additionally, the potential exacerbation of periodontitis through ferroptosis in systemic diseases such as Alzheimer’s disease, nonalcoholic steatohepatitis, chronic obstructive pulmonary disease, and type 2 diabetes is discussed. This review aims to provide new theoretical foundations and strategies for the treatment of periodontitis.